Diversität in Rechtswissenschaft und Rechtspraxis Ein Essay - Grünberger, Michael (2021)
German law schools and legal practice are significantly less diverse than society; in particular, people of colour are missing. The empirical findings so far allow a first analysis of the factors that contribute to the current homogeneity. The legal system not only lacks diverse perspectives, the diversity deficit can also lead to problems for social acceptance and legitimacy. The essay proposes measures for equal participation in the legal professions and invites to an exchange about diversity as a current and pressing challenge for scholarship and practice. The text is an invitation for joint action, but also for reflection and further research.